The course of respiratory tract infections in pediatric hemato-oncology patients during and after the COVID-19 pandemic: single center retrospective cohort study - Düzenli Kar, Yeter; Sağlık, İmran; Aksoy, Gökalp Rüstem; Ağca, Harun; Temuroğlu, Aytül; Mete, Cem Uğur; Sezgin Evim, Melike; Beygo, Büşra Safiye; Aydoğan, Ahmet İbrahim; Ödek, Çağlar; Çelebi, Solmaz; Hacımustafaoğlu, Mustafa; et al. (Frontiers in Pediatrics, 2026)
IntroductionRespiratory tract infections (RTI) are a leading cause of hospitalization in children and remain a significant contributor to morbidity. Our study aimed to examine the epidemiology of RTI in children with hemato-oncologic disease during and after the coronavirus 2019 (COVID-19) pandemic.MethodsThis retrospective study evaluated nasopharyngeal swab samples that were tested using multiplex PCR from 185 children hospitalized with respiratory symptoms between January 2020 and March 2025.ResultsA total of 313 RTI agents were identified in 185 children with hemato-oncologic disorders across 271 infectious episodes. The median age was 6 years. The infection rates for upper respiratory tract infections (URTI) and lower respiratory tract infections (LRTI) were 45% and 55%, respectively. A statistically significant difference was found between patients with URTI and LRTI in terms of CRP, tachypnea, dyspnea, duration of fever, duration of hospital stay due to infection, need for intensive care unit, and oxygen requirements (p < 0.05). The most common pathogens causing RTI were rhinovirus/enterovirus and influenza A/B, and their frequencies increased significantly in the post-pandemic period. Co-infections were significantly more common in the LRTI group during the post-pandemic period. Nine out of 185 children (5%) died.ConclusionChildren with hematologic-oncologic disease are at risk for RTI. The most common agent was found to be rhinovirus/enterovirus. RTI outbreaks were observed especially as a result of the reductions in non-pharmacological measures implemented during the pandemic. In our study, the largest RTI outbreak was seen between November 2023 and May 2024 following the end of the COVID-19 pandemic.